Overall Dietary Intake and Prognosis after Breast Cancer: A Systematic Review. (17th February 2018) - Terranova, Caroline O.; Protani, Melinda M.; Reeves, Marina M.
ABSTRACT: Breast cancer survivors often seek information about how lifestyle factors, such as diet, may influence their prognosis. Previous studies have reviewed evidence around single nutrients, individual foods or food groups. We reviewed studies examining relationships between overall dietary intake and prognosis in breast cancer survivors. A systematic search was conducted to identify studies, published until June 2016, which assessed associations between overall dietary intake (i.e., quality; score; pattern) and mortality and/or recurrence in breast cancer survivors. We identified seven eligible studies. Studies were heterogeneous regarding diet assessment timing (before/after diagnosis); mean age and menopausal status; and dietary intake measure (statistically derived/ a priori defined indices). Better overall dietary intake (i.e., better quality; healthy/prudent pattern; less inflammatory diet) was associated with decreased risk of overall and non-breast cancer mortality, in most studies. Insufficient evidence is available to draw conclusions regarding breast cancer-specific survival and disease recurrence. Following breast cancer diagnosis, better overall dietary intake may independently improve overall and non-breast cancer survival. Survivors may improve prognosis by adopting more healthful dietary patterns consistent with dietary guidelines and/or prudent diet. Future adequately powered studies should consider measuring dietary intake consistently to better understand the role of diet in disease-specific outcomes.